2015
DOI: 10.1149/2.1001508jes
|View full text |Cite
|
Sign up to set email alerts
|

Alloy Design to Prevent Intergranular Corrosion of Low-Cr Ferritic Stainless Steel with Weak Carbide Formers

Abstract: Effect of weak carbide formers, Mo, Mn and Si, on intergranular corrosion (IGC) of low-Cr ferritic stainless steel is analyzed after IGC test using TEM and three dimensional atom probe. The co-addition of Mo, Mn and Si to low-Cr ferritic stainless steel effectively prevents IGC by forming along grain boundaries CMn 4 MoSi intermetallic compounds, which act not only as carbon trap sites but also as diffusion barrier against solute Cr diffusion toward grain boundaries. The low solubility of Cr in the CMn 4 The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 31 publications
(72 reference statements)
0
7
0
Order By: Relevance
“…The test was finished at the opencircuit potential where the scan was originally initiated. In this experiment, the scan rate of 1 mV/s was lower than 1.67 mV/s reported by Kim et al [12] and Park et al [20] J o u r n a l P r e -p r o o f 7 ensuring that the passive film on the Cr-depleted zone along the grain boundaries could be fully reactivated during the reverse scan loop. Similarly, the higher concentration of KSCN provides the sufficiently aggressive corrosion attack and good selectivity [45].…”
Section: Electrochemical Corrosion Testingmentioning
confidence: 60%
See 1 more Smart Citation
“…The test was finished at the opencircuit potential where the scan was originally initiated. In this experiment, the scan rate of 1 mV/s was lower than 1.67 mV/s reported by Kim et al [12] and Park et al [20] J o u r n a l P r e -p r o o f 7 ensuring that the passive film on the Cr-depleted zone along the grain boundaries could be fully reactivated during the reverse scan loop. Similarly, the higher concentration of KSCN provides the sufficiently aggressive corrosion attack and good selectivity [45].…”
Section: Electrochemical Corrosion Testingmentioning
confidence: 60%
“…The formation of the Cr-depleted zone caused by the precipitation of Cr-rich carbides at grain boundaries has been widely studied during the past few decades [4][5][6][7][8][9][10][11]. It was recently reported by Kim et al that Cr-depletion occurs due to the segregation of un-reacted Cr atoms around the carbides of the stabilizing elements (Ti or Nb) along the grain boundaries, but not due to the formation of Cr-rich carbides [12][13][14][15][16][17][18][19][20], which extends the understanding of the mechanism of IGC. Both the conventional sensitization theory and the mechanism proposed by Kim et al agree with the deleterious effect of the carbides, Cr-rich carbide or carbides of the stabilizing elements (Ti, Nb), on the formation of Cr-depleted zone leading to IGC.…”
Section: Introductionmentioning
confidence: 99%
“…1 With the increase of the nitrogen content in the steel, the susceptibility to intergranular attack became more serious, when the nitrogen content increased up to 0.045wt.%, the tendency was no more obvious. 2 The Ra values increased with the extension of sensitization time, low nitrogen content has a beneficial effect on inhibition of this trend. 3 The precipitation of V(C, N) improved the intergranular corrosion resistance to some extent, especially in the stainless steels contained low nitrogen.…”
Section: Resultsmentioning
confidence: 89%
“…It was concluded that the addition of Zr as a stabilizer to low-Cr FSS formed a mixture of ZrC + Fe 23 Zr 6 precipitates which can effectively prevent IGC in two ways: as a strong carbide former to suppress the formation of Cr-carbide and as a diffusion barrier against the diffusion of solute Cr towards the grain boundary. Jin Ho Park et al [2] also put forward some other concepts to prevent the IGC of FSS such as adding Mo, Mn and Si to low-Cr ferritic stainless, which formed CMn 4 MoSi intermetallic compounds, acting not only as carbon trap sites but also as diffusion barrier against solute Cr diffusion toward grain boundaries. Jeong Kil Kim et al [3] did some research on the effect of chromium content on intergranular corrosion and precipitation of Ti-stabilized ferritic stainless steels and found that the increase in Cr content improved IGC resistance as temperature and time for the sensitization became higher and longer, respectively, but it did not prevent IGC.…”
Section: Introductionmentioning
confidence: 99%
“…They have been long recognized to be induced by the boundary sensitization, i.e., the existence of a chromium (Cr) depleted zone adjacent to boundaries [1][2][3]. Even though other underlying mechanisms [4][5][6] for the formation of a Cr-depleted zone are found, the precipitation of Cr-rich carbide and nitride at boundaries is certainly the major one [7,8]. Provided a sufficient chemical driving force for precipitation, this is conceivable since the interface energy for nucleation is comparatively large at boundaries and the subsequent growth would drain Cr atoms from neighboring areas alongside the boundaries [9].…”
Section: Introductionmentioning
confidence: 99%